Photon Upconversion Spectroscopy - Singh P.; Singh P.; Singh S.K. (My University, 2025)
This chapter discusses photon upconversion spectroscopy technique, which is a nonlinear spectroscopy technique that converts low energy photons into high energy photons. It is different from two photon absorption (TPA) and simple harmonic generation (SHG) upconversion processes as it is observed through the involvement of sequential absorption of incident photons between real stationary states. Due to this unique feature, the non-linear upconversion emission can be achieved at very low pump power (few mW) through continuous wave laser. Lanthanide ions doped in different hosts (e.g. oxides, garnets, orthoniobates, fluorides, etc.) are the most suitable activators to achieve photon upconversion emission. This chapter gives a brief description of theoretical background as well as detailed description of experimental setup for photon upconversion spectroscopy. In the end, it also covers a few model examples to achieve photon upconversion emission and their applications in different important areas such as for bio-imaging, sensing, lighting and display, security, etc. © 2021, The Author(s), under exclusive license to Springer Nature Singapore Pte Ltd.